The Role of the Episcopate of the Catholic Church in Moderating the Political Transformations in Poland - Witold Jedynak (European Scientific Journal, ESJ, 2018)
Communism is the ideology which aims at exterminating all religions as, it is believed, they are harmful to social life. Therefore, after the 2nd World War, under the arrangements between the allies, communists took control in Poland and started to gradually but systematically eliminate the influence of the Church and the Catholic religion on the society. Due to the confrontational attitude of the ruling party towards the Church, the relations between the Polish Episcopate and the communist authorities were dominated by the permanent, mainly ideological, conflicts. The breakthrough happened as late as in the 80s of 20th century. At that time, not only did the relations between the former enemies improve but they both started to work together towards the normalization and humanization of the relations between the communist regime and the Episcopate. The result was the participation of the representatives of the Episcopate in the behind-closed-doors negotiations in Magdalenka which happened before the deal between the government and a part of the Solidarity opposition was signed at “the round table”. The main aim of this publication is to present the role of the Episcopate in the process of the political changes in Poland. In the 80s, the Episcopate constituted a specific and unique social group which brought together hierarchs who had various attitudes towards the communist authorities. What caused the internal tensions and divisions within the Episcopate were the Church representatives making deals with the former oppressors as well as various attitudes of bishops towards the ruling party. On the basis of the secondary sources, the author of the publication will attempt to present the role of the Episcope in the moderation of the agreements which became the backbone of the political changes in Poland, i.e. the transformation of communism into post-communism.